High‐Q metallic Fano metamaterial for highly efficient Cerenkov lasing - Kim, Seontae (2020)
A high‐quality‐factor (high‐Q) metallic Fano metamaterial is demonstrated both experimentally and theoretically. This material is suitable for highly efficient Cerenkov lasing in which subwavelength metallic slits are arranged to form asymmetric unit cells. In contrast to conventional dielectric Cerenkov or Smith–Purcell devices, in the proposed device, convection electrons traverse the high‐Q metallic metamaterial. The interplay between an extremely low group velocity from the infinite transverse permittivity of the anisotropic metamaterial and the subradiant damping from a Fano‐type slit mode is shown to be responsible for the high‐Q value, which is measured to be unprecedented at 700. The resulting improvement in the Cerenkov lasing efficiency is estimated to be more than two orders of magnitude using a particle‐in‐cell simulation.